"Avaliação da cultura de segurança do paciente em unidades de neonatologia na perspectiva da equipe multiprofissional" - Karine Antunes Marques Notaro (2017)
Patient safety is a worldwide topic of discussion and a key element in the different levels of health care. Neonatal Intensive Care Units (NICUs) are an environment highly vulnerable for neonates and the effort to enhance safety culture is always among the main strategies to optimize patient safety. Therefore, to understand factors that influence patient safety and to promote patient safety culture assessment are preponderant actions for planning and reorganizing the work process at NICUs. Objective: To analyze the patient safety culture in three public hospitals NICUs from the multi-professional health care teams perspective. Metodology: This is a quantitative transversal survey conducted in three public hospitals NICUs in Minas Gerais state. Data collection was done through the application of the validated instrument, Hospital Survey on Patient Safety Culture (HSOPSC), in 514 personnel of the multi-professional health care team, including nurses, nursing technicians, nursing assistants, physicians, speech therapists, physiotherapists, psychologists, occupational therapists, and social workers. The Software R 3.3.2 and statistic tests Mann-Whitney, Kruskall-Wallis, and Sperman correlation were used for data analyses. Results: Although the collected data did not show any dimension with strengths, some dimensions presented opportunities for enhancement. Dimensions with the highest percentage of positive responses were Teamwork Within Units (59.44%), Supervisor/Manager Expectations and Actions Promoting Patient Safety (49.90%), and Organizational Learning - Continuous Improvement (49,29%). Dimensions with the highest percentage of negative responses were Nonpunitive Response to Error (55.45%), Overall Perceptions of Patient Safety (43.63%), and Staffing (40.86%). The data collection instrument also presented culture outcome variables. One of which was the professional's perception about patient safety, in which 47.96% of the respondents evaluated the safety culture as Regular and 39.8% considered safety as Very good. Among the respondents, physicians, nursing technicians, and nursing assistants are the ones with the highest patient safety culture evaluation. Regarding the number of events reported to the supervisor / manager in the last 12 months, 75.41% of the respondents stated that they had not filled out any notifications during this period, and nurses were responsible for the highest percentage of notifications. It was also possible to establish significant positive and negative correlations between indicators and dimensions of patient safety culture. In addition, the study revealed significant differences among the three NICUs surveyed and none of them presented strengths in the patient safety culture. 9 Conclusion: The findings of this study unveil that the patient safety culture is fragile in NICUs, but with potential opportunities that can become strengths. For accomplish so, it is necessary to invest in this topic, aiming strategies and behavioral changes that could bring effectiveness to the safe work process at the NICUs.